Optimasi Biaya Transportasi Pengiriman Garam Menggunakan Vogel’s Approximation Method (Studi Kasus: PT. Unichem Candi Indonesia) - Nurul Hidayah; Desi Hartati (Prodi Sistem Informasi FST Universitas Jambi, 2023)
Transportation modeling is one of the methods in operations research used to solve transportation problems by considering various variables and constraints. PT. Unichem Candi Indonesia, which has three factories in different locations, faces a transportation problem in the process of delivering salt from its salt-producing regions. This type of research is applied research that employs a quantitative approach. The objective of this research is to determine the minimal transportation cost while taking into account the demand for salt at each factory. The method used to solve this transportation problem is Vogel’s Approximation Method (VAM) to find the optimal solution. The manual data processing using VAM resulted in a cost of Rp. 45,654,851,000. The researchers also used software such as POM-QM, RStudio, and Google Colab (Python) to validate the accuracy of the manual calculations, and it produced the same result of the minimal cost incurred by PT. Unichem Candi Indonesia for transporting salt from the salt source regions to the destination factories, which is Rp. 45,654,851,000.